ANALISIS WACANA BERITA KONTROVERSI PUISI SUKMAWATI SOEKARNOPUTRI DALAM PROGRAM APA KABAR INDONESIA PAGI TVONE (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This thesis discusses the controversy about the reading of Sukmawati Soekarnoputri's poetry in the program Apa Kabar Indonesia Pagi TvOne aired on April 4, 2018. In addition, this research also intends to find out how TvOne represents Sukmawati Soekarnoputri and its representation in the news program of Apa Kabar Indonesia Pagi. The results of the research are the results of the analysis of the program Apa Kabar Indonesia Pagi TvOne, when analyzed using discourse analysis of Teun A. Van Dijk from text elements. The program discusses the reading of Sukmawati Soekarnoputri’s in a discourse that is considered to corner Islam, which compares Indonesian culture to Islamic law. The representation displayed in the discourse shows that Sukmawati is seen as an unprofessional figure because of her controversial poetry, in which the poetry contains elements of SARA and does not pay attention to the values held by society.